2020
DOI: 10.3390/ijms21020661
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Affects HSP60 Folding Activity and Levels in Neuroblastoma Cells

Abstract: The fundamental challenge in fighting cancer is the development of protective agents able to interfere with the classical pathways of malignant transformation, such as extracellular matrix remodeling, epithelial–mesenchymal transition and, alteration of protein homeostasis. In the tumors of the brain, proteotoxic stress represents one of the main triggering agents for cell transformation. Curcumin is a natural compound with anti-inflammatory and anti-cancer properties with promising potential for the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Curcumin is a plant-derived polyphenol that has been proposed as a promising candidate for the development of preventive and therapeutic approaches for many diseases, including neurodegenerative disorders ( 36 40 ). However, curcumin therapeutic application for AD and other neurodegenerative diseases is challenging due to its poor water solubility and low oral bioavailability ( 41 , 42 ).…”
mentioning
confidence: 99%
“…Curcumin is a plant-derived polyphenol that has been proposed as a promising candidate for the development of preventive and therapeutic approaches for many diseases, including neurodegenerative disorders ( 36 40 ). However, curcumin therapeutic application for AD and other neurodegenerative diseases is challenging due to its poor water solubility and low oral bioavailability ( 41 , 42 ).…”
mentioning
confidence: 99%
“…Some possibilities are to (i) identify compounds and/or methods that will induce a antitumor immune response by promoting the presence of Hsp60 on the surface of tumor-cells [172]; (ii) develop Hsp60 vaccines exploiting its potential for inducing the production of cytokines by interaction with monocytes and macrophages, and by manipulating its ability to bind and activate TLR-2 in CD4+CD25+ regulatory T cells and TLR-4 in B cells [173]; and (iii) identify compounds able to modulate Hsp60 expression, in order to reduce or enhance its activity in those tumors in which it displays a pro-or anti-tumorigenic role, respectively. Understanding the mode of action of Hsp60 and its regulation by miRNAs in different tissue and tumor types will help in the development of novel therapeutic strategies for cancer therapy [68,112,174]. Moreover, the utilization of advanced drug delivery systems, as exosome-like vesicles promise to be, to deliver molecules, such as miRNAs known to regulate Hsp60, and internalize them in the target cells, should be actively investigated to standardize the particles and their contents as well as their isolation from cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It puts Hsp60 in the stage's center and presents it as a target for developing treatment strategies aimed at inhibiting-blocking this collaborator with the enemy from the inside. For example, Hsp60 downregulation by chemical compounds suppressed cancer-cell proliferation and tumor progression and enhanced the beneficial effects of anti-cancer treatments [62,69,90,[108][109][110][111][112]. It was observed that Hsp60 knockdown inhibited tumor progression by altering mitochondrial homeostasis and inactivating the mTOR pathway, in ovarian cancer and glioblastoma [90,109].…”
Section: Hsp60 In Carcinogenesismentioning
confidence: 99%
“…This issue needs to be clarified in future research. Considering the pleotropic effect of curcumin on neurodegenerative diseases, cancers and immune disorders, curcumin is a promising substance for treating disease today without causal treatment [1,2,10,[51][52][53][54][55][56][57]. In addition, it is a safe, inexpensive substance, easily accessible and penetrates the blood-brain barrier and neuronal membranes, which is its great advantage [1][2][3]7].…”
Section: Discussionmentioning
confidence: 99%